Ideomotor apraxia without aphasia and aphasia without apraxia: the anatomical support for a double dissociation. Issue 3 (March 1993) - Papagno, C; Della Sala, S; Basso, A
Abstract : This study aimed to verify the existence of a double aphasia/apraxia dissociation. Apraxic patients without aphasia and aphasic patients without apraxia were included in a consecutive series of patients with cortical or subcortical CT documented vascular lesions in the left hemisphere. Of 699 patients, 10 were found to be apraxic but not aphasic and 149 aphasic but not apraxic. These findings indicate an aphasia/apraxia double dissociation. This suggests that praxis and language make use of two different, partly overlapping networks.